Design of an Android-based Sundanese Javanese Regional Language Learning Application - Ridho Ichvan Gusta Aryatama; Muhammad Fachrie (SEAN Institute, 2023)
Along with the development of smartphone technology, it has become an option for learning needs. With so many types of regional language learning, it is of interest to most people from outside the region. The regional languages of Java and Sunda are mostly in demand by people from outside the region. Based on the large amount of interest in learning regional languages, the Jasun Regional Language Learning Application is the choice of researchers. In this study, the SDLC method was used with a prototype model. By using the prototype model, the author as well as the developer can find out the specifications of the user's needs in more detail and the prototype model is suitable for making small applications. With the development of the Sundanese Javanese Regional Language learning application, it is hoped that it will make it easier for people who want to learn Javanese and Sundanese Regional Languages. That way learning Javanese and Sundanese Regional Languages does not need to come directly to the area. Simply by using a smartphone as a medium for learning Javanese and Sundanese languages, it can be done anywhere and anytime.